Атоми впровадження у кристалічній гексагональній структурі - Matysina, Z. A.; Zolotarenko, An. D.; Zolotarenko, Ol. D.; Myronenko, T. V.; Schur, D. V.; Rudakova, E. P.; Chymbai, M. V.; Zolotarenko, A. D.; Zagorulko, I. V.; Havryliuk, O. O. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2023)
As part of the work, the hexagonal structure of B19 type metals as hydrogen sorbents will be considered. That is, crystal lattices are considered, where atoms of impurities (hydrogen) are introduced into the interstices of the metal. To do this, we present an image of the B19 structure itself. In this work, the solubility of hydrogen in the crystal structure of B19 type metals was studied using the configuration method, and the dependence on the composition of the alloy and temperature was found in the substitution of nodes and interstices. Also, in the work the degrees of long-range order at the nodes are considered and the parameters of the correlation in the substitution are determined. A graphical view of the effect of atomic order on the solubility of impurities is given. The calculated data obtained in the work coincide with the experimental data of other studies, and the obtained calculation formulas make it possible to determine the energy parameters of the alloys, which is a certain scientific value of the work. The proposed system takes into account only atomic interaction and absorption (dissolution) and diffusion of interstitial atoms into the bulk of the crystal structure; therefore, it is possible to predict the introduction of only a hydrogen atom. Thus, the results obtained in the work of the correlation parameters for the distribution of atoms only in octapores or only in tetrapores allow a deeper study of the physical characteristics of alloys of the B19 type and an understanding of the processes of hydrogen sorption by the working bodies of hydrogen storage.